Association of orthodontic treatment and aspiration pneumonia - Sawas, Mohamed Ali; Alenezi, Nada Murdi; Alshahrani, Ayesha Nasser; Al-Hammoud, Salma Taher; Asiri, Mohammed Abdullah; Alodan, Yara Abdulaziz; Alghamdi, Ali Mohammed; Alghamdi, Moteeb Abdullah; Alsharif, Omar Abdoullah; Assiri, Mohammad Yahya; Fayyumi, Shahad Hassan (International Journal Of Community Medicine And Public Health, 2022)
Foreign body aspiration or ingestion is an uncommon potential complication during orthodontic dentistry, and it can produce a medical emergency. Obstruction of the airways can be life-threatening, and delayed recognition and management can result in pulmonary complications such as recurrent pneumonia. Dental treatment has been identified as an important cause of the misplacement of foreign bodies in the airway. Objects used in orthodontic treatment are mainly used due to their manufacturing limitations, such as their shape and size, and because they are made of radiolucent materials, which make them easy to aspirate or ingest and difficult to detect with a radiograph. However, few reports have been published on orthodontic dentistry-related foreign body aspiration and pulmonary complications. Furthermore, micro-aspiration due to poor oral hygiene in patients undergoing orthodontic procedures has been investigated in this review since poor oral hygiene is a well-established risk factor for aspiration pneumonia in the elderly population. The association between the aspiration of orthodontic material and aspiration pneumonia is not well established. Aspiration pneumonia is a secondary symptom of misdiagnosis or delayed diagnosis of dental material aspiration. Additionally, poor oral hygiene can also increase the risk of aspiration pneumonia in elderly patients since poor oral hygiene during orthodontic treatment leads to plaque retention, which can lead to increased development of hyperplastic gingivitis and periodontal breakdown, established risk factor for aspiration pneumonia.